Challenges of the Digital Economy: Assessing the Level of Competence of Technical Universities Graduates Based on Pedagogical Testing - Lyudmila I. MIRONOVA; Olga V. RUZAKOVA (Communications of International Proceedings, 2020)
According to the Federal state educational standard of higher education in the learning process of students the competence-based approach should be implemented. It means that it is necessary to be able to determine the level of formation of students’ competence in different subject domain. The purpose of the article is to describe the methods of levels determination of students’ competences formation as a result of the development of the discipline, allowing them to assess, using a level approach (low, medium, base, high). The competence of the student of concrete subject domain is understood as his theoretical knowledge and abilities in the studied subject domain and practical experience of their application. The main stages of the proposed methodology: the input diagnostic test before studying the course, the final pedagogical testing after the course, the defense of the project which is independently executed by the student. The criteria of Kruskal-Wallis and Bartlett were used for an assessment of the results homogeneity of pedagogical testing, and the criterion of Pearson's Chi-squared was used for the level evaluation of students’ experience in project developing. The algorithm of application of the methodology is presented in specific numerical data. The technique can be used during studying disciplines, which are ending by independent development of students’ projects, such as: term paper, final qualification work, a thesis project, master's dissertation, etc.
Keywords: Digitalization of The Economy; Engineering Training; Statistical Processing of The Results of Pedagogical Testing; The Level of Competence Formation.